Ответ(ы) на вопрос:
3
b/[a(b-5a)]-(15b-25a)/[(b-5a)(b+5a)]=(b²+5ab-15ab+25a²)/[a(b-5a)(b+5a)]=
=(b²-10ab+25a²)/[a(b-5a)(b+5a)]=(b-5a)²/[a(b-5a)(b+5a)]=(b-5a)/[a(b+5)]
4
3a-a/4=(12a-a)/4=11a/4=2 3/4*a
[latex] \frac{b}{ab-5a^2} -\frac{15b-25a}{b^2-25a^2}=\frac{b}{a(b-5a)}-\frac{5(3b-5a)}{(b-5a)(b+5a)} =\\\\= \frac{b(b+5a)-5a(3b-5a)}{a(b-5a)(b+5a)} = \frac{b^2+5ab-15ab+25a^2}{a(b-5a)(b+5a)} = \frac{b^2-10ab+25a^2}{a(b-5a)(b+5a)} =\\\\= \frac{(b-5a)^2}{a(b-5a)(b+5a)} = \frac{b-5a}{a(b+5a)} \; ;\\\\\\3a- \frac{a}{4}= \frac{12a-a}{4} =\frac{11a}{4}=2\frac{3}{4}\, a=2,75\,a [/latex]
Не нашли ответ?
Похожие вопросы